2012
DOI: 10.5539/ijbm.v7n9p120
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Effects of Political Skills Dimensions on Employee Performance

Abstract: The main objective to conduct this research is to examine that how employee performance could be increase by the impact of different dimensions of political skills. To examine how employee performance can be affected by mediation relationship of four different dimensions of political skills if those dimensions directly related with proactive personality. The finding shows positive significant relation between proactive personality and employee performance having dimensions of political skills as mediator as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Supervisor-rated performance reflects a supervisor's subjective perception about their followers rather than the actual level of their performance. Other studies have found a positive relationship between political skill and subjective individual performance (Blickle et al 2011d;Chaudhry et al 2012;Wei et al 2012), and recent meta-analyses have confirmed a positive relationship between political skill and in-role as well as extra-role performance (Bing et al 2011;Munyon et al 2014). Moreover, they usually exude a calm self-confidence, which is perceived by others as a sign of competence and credibility.…”
Section: Political Skill and Individual Performancementioning
confidence: 85%
See 2 more Smart Citations
“…Supervisor-rated performance reflects a supervisor's subjective perception about their followers rather than the actual level of their performance. Other studies have found a positive relationship between political skill and subjective individual performance (Blickle et al 2011d;Chaudhry et al 2012;Wei et al 2012), and recent meta-analyses have confirmed a positive relationship between political skill and in-role as well as extra-role performance (Bing et al 2011;Munyon et al 2014). Moreover, they usually exude a calm self-confidence, which is perceived by others as a sign of competence and credibility.…”
Section: Political Skill and Individual Performancementioning
confidence: 85%
“…Blickle et al (2012b) revealed a positive relationship between the political skill of salespersons and their objective performance, suggesting that there is validity in the social capital perspective. Other studies have found a positive relationship between political skill and subjective individual performance (Blickle et al 2011d;Chaudhry et al 2012;Wei et al 2012), and recent meta-analyses have confirmed a positive relationship between political skill and in-role as well as extra-role performance (Bing et al 2011;Munyon et al 2014).…”
Section: Political Skill and Individual Performancementioning
confidence: 87%
See 1 more Smart Citation
“…employees' behaviors and attitudes (Kimura 2014). Past research showed that there is a positive relationship between political skill and job satisfaction (Ferris et al 2007;Ferris et al 2009), job performance (Ferris et al 2007;Hochwarter et al 2007;Blickle, Below & Johannen 2011;Chaudhry, Ashraf & Jaffri 2012;Wei, Chiang & Wu 2012;Bing et al 2011;Munyon et al 2014), organizational citizenship behaviors , and organizational commitment. Past studies also indicated a negative relationship between political skill and turnover intentions (Banister & Meriac 2014).…”
Section: Introductionmentioning
confidence: 98%
“…It has been seen that in a developing country like Pakistan political skill construct is in infancy stages and very few evidences are available that examined its mediating mechanism (Chaudhry, Rehman, Ashraf, & Jaffri, 2012;Jam, Khan, Zaidi, & Muzzafar, 2011). Based on the identified gaps and the recommendations of Munyoun et al (2015) on investigating impact of political skill on helping and knowledge sharing behavior in presence of organizational based self-esteem-the present study is carried out in the banking sector of Islamabad and Rawalpindi.…”
Section: Introductionmentioning
confidence: 99%